The Role of Customer Engagement in Mediating The Effect of Service Quality on Customer Loyalty - Rizki Iskandar Rustam; Devan Tribowo; Sandriana Marina (Green Publisher, 2025)
Competition drives courier service companies to work harder to serve the quality of their services. However, customer involvement is necessary to enhance customer loyalty. This study investigates the mediating role of customer engagement in the relationship between service quality and customer loyalty in Paxel’s courier services. The objective of this study enhances the impact of service quality on loyalty. Data were collected through questionnaries from a sample of 190 Paxel users with respondents meeting the criteria of having a minimum education of high school and having used Paxel’s services at least twice. The findings indicate that service quality significantly affects loyalty both directly and through customer engagement, emphasizing the critical role of engagement. The study concludes that improving service quality and actively engaging customers are essential strategies for strengthening loyalty, offering valuable insights for practitioners and researchers in the service industry. Especially in courier service.